2020
DOI: 10.1101/2020.05.15.20095927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disparities in COVID-19 Reported Incidence, Knowledge, and Behavior

Abstract: Background: Data from the COVID-19 pandemic in the United States show large differences in hospitalizations and mortality across race and geography. However, there is limited data on health information, beliefs, and behaviors that might indicate different exposure to risk. Methods: A sample of 5,198 respondents in the United States (80% population representative, 20% oversample of hotspot areas in New York City, Seattle, New Orleans, and Detroit) was conducted from March 29th to April 13th to measure differenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
0
2
1
Order By: Relevance
“…Data from this study revealed that males showed a slight increase in the level of awareness (60%) compared to female participants (57%). Our finding was different to a similar study conducted in USA, in where better awareness was found in women compared to men [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Data from this study revealed that males showed a slight increase in the level of awareness (60%) compared to female participants (57%). Our finding was different to a similar study conducted in USA, in where better awareness was found in women compared to men [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, females felt more vulnerable than males to the disease [ 66 ]. Furthermore, Cutler et al [ 67 ] reported that U.S. males are less likely to know how COVID-19 is spread or the exact symptoms of the disease, while Karijo et al [ 68 ] supported that females were more likely to name correctly the symptoms of the coronavirus than males.…”
Section: Discussionmentioning
confidence: 99%
“…In general, individuals of lower SES have less health-related knowledge (Phelan et al, 2010). Supporting this idea, research early in the COVID-19 crisis found lower COVID-related knowledge among individuals of lower SES (Cutler, Stantcheva, Alsan, & Yang, 2020).…”
Section: Ses and Well-being During The Pandemicmentioning
confidence: 92%